2014
DOI: 10.1186/1746-6148-10-121
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and pathological insights into Chlamydia pecorum-associated sporadic bovine encephalomyelitis (SBE) in Western Australia

Abstract: BackgroundDespite its global recognition as a ruminant pathogen, cases of Chlamydia pecorum infection in Australian livestock are poorly documented. In this report, a C. pecorum specific Multi Locus Sequence Analysis scheme was used to characterise the C. pecorum strains implicated in two cases of sporadic bovine encephalomyelitis confirmed by necropsy, histopathology and immunohistochemistry. This report provides the first molecular evidence for the presence of mixed infections of C. pecorum strains in Austra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 30 publications
3
42
0
Order By: Relevance
“…4). Our group previously provided evidence to suggest that genetically similar, if not identical, strains of C. pecorum can be found in Australian sheep, cattle, and koalas (6,8,39). The whole-genome phylogenies constructed for the strains sequenced from northern New South Wales (Gun/koa1/Ure) and South Australian koalas (SA/k2/UTG) appear to confirm this finding.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…4). Our group previously provided evidence to suggest that genetically similar, if not identical, strains of C. pecorum can be found in Australian sheep, cattle, and koalas (6,8,39). The whole-genome phylogenies constructed for the strains sequenced from northern New South Wales (Gun/koa1/Ure) and South Australian koalas (SA/k2/UTG) appear to confirm this finding.…”
Section: Discussionsupporting
confidence: 62%
“…In the case of C. pecorum specifically, a previous MLST study on livestock C. pecorum strains showed that a single animal could be infected by multiple strains at different anatomical sites, with speculation only on shedding multiple strains from the same site (8,39). However, this is the first study to reveal the presence of multiple C. pecorum strains at the same anatomical site in both koalas and sheep.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…65 By IHC, chlamydial antigen can be demonstrated in the cytoplasm of the endothelium and macrophages of brain, spleen and lung and in the mesothelium. 72 Typing of C. pecorum strains revealed differences between strains detected in brain, heart, lung, liver and the intestine, suggesting that different strains may have different pathogenic potential, an observation that was previously also suggested from studies of sheep. 73 Associations between C. pecorum infection and enteritis or reproductive diseases such as placentitis and abortion, vaginitis, endometritis, mastitis, and orchitis have been reported with shedding of the organism through the fecal or vaginal route.…”
Section: Chlamydia Pecorum In Ruminantsmentioning
confidence: 63%
“…Even today, with whole genome sequencing readily available, MLST is still often used as the first point to barcode a strain 13 . In an effort to evaluate the overall genetic diversity and relationships between Australian koala, sheep and cattle C. pecorum strains, we developed and applied a C. pecorum-specific MLST to a range of isolates and C. pecorum-positive clinical samples from koalas, Australian sheep and cattle [14][15][16] .…”
Section: Pecorum Molecular Epidemiologymentioning
confidence: 99%